(untitled) (Fiep Bulletin - online, 2015)
The aim of this study was to investigate the effects of the Gymnastics through intervention with application of stretching exercises and relaxation to the commerce of Dourados-MS, in order to help reduce the physical fatigue due to long hours in a workday. The sample consisted of 42 people, both gender, aged between 18 and 60, with the application of test and retest, interspersed with intervention, with 15 minutes twice a week at the beginning of the workday, which characterizes as a preparatory Gymnastics. With the intervention, it was found some improvement for complaints of pain in the arms and neck region and significant reduction in medical visits during the intervention, showing the benefits with the implementation of the Gymnastics program among the sample. It could be concluded that, with the program organized and implemented according to the workers’ needs there was reduction in the physical fatigue and also the improvement of the willingness to perform the tasks in the workweek with fewer complaints of pain.